A first absolute chronology for Late Neolithic to Early Bronze Age Myanmar: new AMS 14C dates from Nyaung'gan and Oakaie. (27th June 2018) - Pryce, Thomas Oliver; Kyaw, Aung Aung; Kyaw, Myo Min; Win, Tin Tin; Win, Thu Thu; Win, Khin Htwe; Mon, May Myat; Aye, Mar Mar; Htay, Su Hlaing; Mar, Aye Aye; Bellina, Bérénice; Bentley, R. Alexander; et al.
Abstract: Abstract : Late prehistoric archaeological research in Myanmar is in a phase of rapid expansion. Recent work by the Mission Archéologique Française au Myanmar aims to establish a reliable Neolithic to Iron Age culture-historical sequence, which can then be compared to surrounding regions of Southeast Asia. Excavations at Nyaung'gan and Oakaie in central Myanmar have provided 52 new AMS dates, which allow the creation of Myanmar's first reliable prehistoric radiometric chronology. They have also identified the Neolithic to Bronze Age transition in central Myanmar, which is of critical importance in understanding long-range interactions at the national, regional and inter-regional level. This research provides the first significant step towards placing late prehistoric Myanmar in its global context.